Métodos de atmosfera controlada dinâmica × 1-MCP: metabolismo e qualidade de maçãs armazenadas - Thewes, Fabio Rodrigo (2019)
Lowering the O2 partial pressures to extremely low levels (< 0.5 kPa) during controlled atmosphere (CA) storage is becoming more and more usually in commercial rooms. However, lowering to much the O2 partial pressure can induce the anaerobic metabolism, with acetaldehyde and ethanol production, compounds that can induce physiological disorders and off-flavours, if in too high concentrations. Thus, to decrease the O2 partial pressure in a save way, it is necessary monitor the lowest O2 limit (LOL) in real time over the storage period, in order to set the O2 partial pressure according to fruit metabolism. This storage system in known as dynamic controlled atmosphere (DCA). Nowadays, there are three DCA methods available commercially: based on ethanol (DCA – EtOH), chlorophyll fluorescence (DCA – CF) and respiratory quotient (DCA – RQ). In this sense, at the present study were developed 5 papers aiming at: [1] evaluate the effect of CA, DCA – CF, DCA – RQ with two low oxygen stresses a week and it’s interaction with 1-MCP on the overall quality, volatile profile and expression of enzymes involved on volatile compounds synthesis; [2] study the effect of DCA – RQ storage on the dynamics of anaerobic metabolism and the induction of sugar-alcohols, such as sorbitol and glycerol, and its relationship with the membrane permeability of apples; [3] develop, calibrate and apply a novel DCA method based on CO2 production of fruit (DCA – CD) to estimate the LOL, aiming at maintain overall quality, enzyme activity, sugars, acids metabolism and the volatile compounds profile under DCA – CD. Furthermore, compare the storage under DCA – CD with DCA – CF, DCA – RQ and 1-MCP treatment. The storage of apples under DCA – RQ 1.5 with two low oxygen stresses a week resulted in fruit with lower ethylene production, higher physical and chemical quality, especially higher esters emission. This is a result of higher level of AAT enzymes genes expression (MdAAT1), even when fruit were treated with 1-MCP, showing that the expression of MdAAT1 genes are not ethylene dependent in fruit stored under DCA – RQ 1.5. Apple stored under DCA – CF had lower volatile accumulation due to lower precursors concentration and expression of enzymes involved in esters (MdAAT1), because reduces the aerobic respiration to a minimum level without the induction of anaerobic metabolism. The storage of apples under DCA – RQ resulted in anaerobic metabolism, accumulating acetaldehyde, ethanol and inducing sorbitol accumulation, decreasing the membrane permeability even under low O2 stress condition. The LOL determination can be performed, in real time, over the storage period by the CO2 production only (DCA – CD). This method allows the O2 set point determination in a dynamic way for several apple cultivars, orchards, without and with 1-MCP treatment, harvest maturity and storage temperature. Apples storage under DCA – CD resulted in similar O2 set points and quality maintenance as compared to DCA – RQ and higher as compared to CA, CA + 1-MCP and DCA – CF, because reduced decay and physiological disorders, maintained higher firmness and healthy fruit amount. Fruit stored under DCA with extremely low oxygen had higher main ester concentration, such as butyl acetate, 2-methylbutyl acetate and hexyl acetate. CA and DCA had no effect on malate concentration, being its concentration more affected by storage time. The Krebs cycle minority acids are significantly affected by the DCA conditions, being its concentration reduced by the storage under low oxygen storage (DCA – RQ 1.5 and DCA – CD 1.3). In general terms, the best long-term apple storage conditions follow this order: DCA – CD = DCA – RQ > DCA – CF = CA + 1-MCP > CA.